Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pengguna Aplikasi Go-Food Selama Pandemik Covid-19 (Studi pada Konsumen Kota Bandung) - Vidina, Nur Suci; Chaniago, Harmon; Gaffar, Mohammad Rizal (Applied Business and Administration Journal, 2022)
The Go-Food application is an application that serves online food and beverage orders made by PT Gojek Indonesia. There are several new policies made by PT Gojek Indonesia to reduce the spread of the COVID-19 pandemic, but there are still some driver partners and merchant partners who have not implemented these policies, such as there are Go-Food drivers who are inconsistent in using masks and gloves. , there is no guarantee for the cleanliness of food or beverage processing from the seller, and the company has not guaranteed the implementation of social distancing for its employees. This study aims to explain whether service quality has an influence on customer satisfaction of Go-Food application users during the COVID-19 pandemic for consumers in Bandung City. This study is a quantitative study with a descriptive method that examines the effect of service quality on customer satisfaction using the Go-Food application during the COVID-19 pandemic on consumers in the City of Bandung. The population used in this study was 912,000 people in the city of Bandung in the young age group (15-34 years) who used the Go-Food application during the COVID-19 pandemic with a total sample of 384 Go-Food consumers during the COVID-19 pandemic. young age group (15-34 years). The sampling technique used is a simple random sampling technique. The data collection technique used in this research is a survey technique through the distribution of online questionnaires via google form. The data of this study were analyzed by simple linear regression method. The results of this study indicate that there is a positive and significant effect on service quality on customer satisfaction using the Go-Food application during the COVID-19 pandemic on consumers in the city of Bandung.